Hampton's Hump: A Notable Radiographic Finding in a Patient with Infectious Endocarditis. (10th December 2021) - Earle, Matthew; Bailey, James; Berkeley, Ross P.
Abstract : Infectious endocarditis is a relatively uncommon entity that may present with a variety of clinical scenarios, ranging from a stable patient with nonspecific symptoms to a critically ill patient suffering from embolic disease. We report a case of an otherwise healthy 35-year-old female who presented to the Emergency Department with gradually progressive dyspnea, weight loss, and lower extremity edema. As part of her initial evaluation, a chest radiograph was performed and demonstrated Hampton's Hump, a peripheral wedge-shaped opacity consistent with a possible pulmonary infarct. Further diagnostic investigation in the Emergency Department led to an unanticipated diagnosis of infectious endocarditis. This case serves as an important reminder that nonspecific diagnostic findings need to be appropriately considered in context and is a rare demonstration of Hampton's Hump associated with infectious endocarditis.